POLARIZATION OF LOCAL COMMUNITY PERCEPTION ON SOCIO-CULTURAL DYNAMICS IN ECOTOURISM DEVELOPMENT OF BOPUNJUR, WEST JAVA - Gatot Widodo; Ricky Avenzora; Elly Malihah; Tutut Sunarminto (Indonesian Journal of Forestry Research, 2023)
In addition to providing multiplier economy benefits, the tourism sector also has the potential to cause some latent and massive negative social impacts. For this reason, it is important to map out the orientation of the local community. This study aims to analyse the polarization of local community's perceptions about socio-cultural dynamics in the ecotourism development area. The local community that became the focus of the research consisted of five groups of respondents, namely traditional leaders, religious leaders, educational leaders, community leaders, and tourism actors. This research was conducted in the Bopunjur Ecotourism Area, Bogor Regency, West Java, precisely in seven ecotourism destinations, namely Ciawi, Caringin, Cibogo, Cipayung, Megamendung, Cisarua, and Tugu. This study used an exploratory – phenomenology approach. Data collection on social and cultural dynamics was carried out by distributing questionnaires to the respondents. The research instrument in the form of a questionnaire designed with a closed ended with guidance on one score one indicator scoring system. The results showed that positive social situations namely conducive situations, associations, cooperative situations, and productive collaborations were still more dominant than negative social situations: war, conflict, and dissociation. The polarization of local community on socio-cultural dynamics has a positive direction with a polarization scale that is aligned with each other so that there is a great opportunity to build productive collaboration between stakeholders in this area.